Infectious uveitis in immunodeficient HIV-negative patients: A retrospective study - Petra Svozilkova; Eva Rihova; Michaela Brichova; Andrea Havlikova; Aneta Klimova; Jarmila Heissigerova (Biomedical Papers, 2020)
Aims: Cases of infectious uveitis in immunodeficient patients may present with atypical clinical features because the clinical course of disease is usually affected by the compromised immune system. Therefore, it is sometimes difficult to determine the correct diagnosis. The aim of this study was to evaluate a prevalence of immunodeficient HIV-negative individuals among patients with infectious uveitis and to assess diagnostic and therapeutic approaches. Methods: A retrospective study. Results: In years 2003-2017, we diagnosed 594 patients with infectious uveitis. In 35 of them, infectious uveitis occurred on the basis of immunodeficiency (malignancy, immunosuppressive therapy etc.). The most common infectious uveitis was cytomegalovirus retinitis, followed by acute retinal necrosis, herpetic anterior uveitis, endogenous fungal endophthalmitis, toxoplasmic retinochoroiditis, progressive outer retinal necrosis and syphilis. In indicated cases, intraocular fluid examination was a valuable diagnostic tool. After initiation of treatment, improvement of BCVA was observed in 13 eyes, stabilization in 13 eyes and deterioration in 11 eyes. In some patients who experienced adverse effects of medication, the recommended doses were decreased. Conclusion: Our experience shows that patients with diagnoses of acute retinal necrosis or progressive outer retinal necrosis have a poor visual prognosis. The occurrence of cytomegalovirus retinitis signifies a very unfavorable survival prognosis in patients who underwent hematopoietic stem cell transplantation; the patients in our study died within 1 year from cytomegalovirus retinitis diagnosis.